A physical data model for spatio-temporal objects. (December 2019) - de Jong, Kor; Karssenberg, Derek
Abstract: Modellers simulating the state of the physical and biological environment using agents and fields, face the challenge of storing the state variables, like the distribution of biomass and the location and properties of animals. These variables differ from each other, depending on how exactly they represent their state. In this paper we describe an approach for storing multiple kinds of representations of model state variables using a unified physical data model. We identified a set of aspects in which these representations differ from each other and which have an implication for the data model. Based on these aspects we defined a physical data model for storing spatio-temporal objects, which we implemented in an open source software library. We illustrate how the resulting data model can be used to store multiple kinds of model state variables and explain how this data model can be useful in environmental modelling software. Highlights: Agent-based and field-based modelling data are handled in a uniform way. All model state can be stored in a single file. The data model is capable of storing temporal and spatial properties of multiple objects. For a single kind of objects properties can be stored that are linked to different time and space domains.